2015
DOI: 10.1038/leu.2015.231
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive human anti-CD83 monoclonal antibody depletion of activated dendritic cells in transplantation

Abstract: Current immunosuppressive/anti-inflammatory agents target the responding effector arm of the immune response and their nonspecific action increases the risk of infection and malignancy. These effects impact on their use in allogeneic haematopoietic cell transplantation and other forms of transplantation. Interventions that target activated dendritic cells (DCs) have the potential to suppress the induction of undesired immune responses (for example, graft versus host disease (GVHD) or transplant rejection) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 37 publications
0
37
1
Order By: Relevance
“…Previous studies have shown that NSG mice engraft human monocytes and DCs when injected with human cord blood, 38 and engraft human monocytes when injected with hPBMCs. 39,40 Similarly, SCID mice injected with hPBMCs engraft human DCs, 41 but the current study is the first to demonstrate DC engraftment in NSG mice injected with hPBMCs. Human T cells recognize murine major histocompatibility complex I and II molecules in NSG mice to cause GVHD, 27 but the identity of the APCs involved remains to be determined.…”
Section: Discussionmentioning
confidence: 67%
“…Previous studies have shown that NSG mice engraft human monocytes and DCs when injected with human cord blood, 38 and engraft human monocytes when injected with hPBMCs. 39,40 Similarly, SCID mice injected with hPBMCs engraft human DCs, 41 but the current study is the first to demonstrate DC engraftment in NSG mice injected with hPBMCs. Human T cells recognize murine major histocompatibility complex I and II molecules in NSG mice to cause GVHD, 27 but the identity of the APCs involved remains to be determined.…”
Section: Discussionmentioning
confidence: 67%
“…By targeting activated DCs, anti-CD83 depleting antibodies can prevent human peripheral blood mononuclear cell-induced acute graft vs. host disease in SCID mouse recipients (30, 31). Although the mechanisms through which membrane-bound CD83 regulates immune responses are still to be elucidated, one of the proposed pathways is though negative regulation of MARCH1 and MARCH8.…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies with activity against molecules that are expressed on activated cells, including DCs, 98 may be effective if they can be administered in the right window after SCT when donor DCs are active and recipient DCs have been eliminated. Of note, because donor APCs are likely crucial for the generation of pathogen-specific immunity, targeting donor DC or APC subsets will need to be studied with caution in the clinic.…”
mentioning
confidence: 99%